Nano-structured sorbents for rapid response interior air humidity buffering applications - Casey, Sean (2013)
Within a closed environment, (e.g. building, car, aircraft) that is thermally and hygrically isolated from the exterior climate, one approach that can help reduce the energy required for indoor mechanical climate control whilst increasing comfort levels for occupants is to use hygrothermal coatings on top of existing materials. Hygrothermal coatings can re-introduce both thermal and hygric buffering within the isolated envelope. Understanding of the behaviour of these coatings allows them to be optimized for different environments. The overall aim of the research is to design the functional properties of inorganic, nano structured surface coatings i.e. mesoporous silica (MS) to produce desired hygrothermal behavioural responses to climatic variables in a controlled environment. This can be achieved through correlation of the hygrothermal properties of desiccant materials with their microstructural characteristics and understanding the hygrothermal behaviour of the materials under representative psychrometric conditions. Stage 1 was to characterise the hygrothermal properties of the MS and other conventional desiccant materials i.e. Silica Gel, Molecular Sieve, Clinoptilolite and Bentonite to produce a ‘Template of functional properties’ and provide material input data for the numerical models. These tests included dynamic vapour sorption (DVS) techniques for moisture absorption including cyclic adsorption/desorption and sorption isotherms, wet-cup tests for vapour permeability, partial immersion tests for liquid water absorption, modified transient plane source (MTPS) tests for thermal conductivity and differential scanning calorimetry (DSC) for heat capacity. Stage 2 utilised techniques to classify the pore geometry of the desiccants, including helium pycnometry for solid density, gravimetric testing for bulk density, N2 physisorption for specific surface area, mesopore volume and mean pore diameter with small angle X-ray scattering and transmission electron microscopy used to corroborate the N2 results. Scanning electron microscopy (SEM) was used to confirm material composition and purity and to indicate macropore distribution. A correlation between the hygrothermal properties from Stage 1 with their microstructural characteristics was then sought. Stage 3 was a parametric analysis of the candidate materials hygrothermal behaviour using the validated 1D numerical simulation software WUFI Pro v5.1. Further analysis was carried out to assess how the numerical model could be used to tune the functional properties of the MS materials to suit differing psychrometric conditions in closed environments. A series of simulations using a representative climate (Nottingham) were also run to compare the hygrothermal behaviour of the MS materials to the conventional desiccants A series of energetic 3D physical and numerical models (WUFI Plus v 2.1) were designed to study the resultant relative humidity levels in both occupied and unoccupied spaces and under different air exchange rates due to the presence of the hygrothermal materials in a closed environment. The 3D model was also used to compare the operational energy usage of different retrofitting cases under the same representative climate used in Stage 3 with three different heating, cooling humidification and dehumidification (HCHD) control scenarios. The MS materials displayed significantly higher Moisture Buffer Values (MBV), equilibrium moisture contents (EMC) and faster response rates when compared to the conventional desiccants. It was shown that WUFI Pro can be used as a design tool for material functional properties, with the sorption isotherm, and in particular adjustment of the w50 – w80 gradient of the absorption branch isotherm being by far the most sensitive parameter. In the MS samples, the dynamic vapour sorption (DVS) response time has a significant and positive logarithmic relationship with both the mesopore diameter and the mesopore volume implying that mesopore geometry can be tuned in order to give the desired dynamic vapour sorption/ desorption response rate and storage capacity to suit a given set of interior psychrometric conditions. It is therefore possible to tune an MS material to suit a particular set of psychrometric conditions using WUFI Pro. The MS materials displayed outstanding passive buffering performance across a range of exterior climate conditions combined with numerous internal moisture and ventilation overloading scenarios, providing constant humidity buffering within the American Society of Heating, Refrigerating and Air Conditioning Engineers (ASHRAE) comfort limits. When compared against a retro-fitted gypsum-lined indoor environment there was a potential reduction in humidification/ dehumidification energy demand of up to 100% when using an MS material coating.